PENINGKATAN KEMAMPUAN PEMAHAMAN DAN PEMECAHAN MASALAH MATEMATIS MELALUI PEMBELAJARAN DENGAN PENDEKATAN KONTEKSTUAL - Muhsin Muhsin; Rahmah Johar; Elah Nurlaelah (Universitas Syiah Kuala, 2013)
Understanding and problem solving of mathematical ability junior high school students is still low, it is one of the main issues in mathematics education. Therefore need approaches that can improve the ability of understanding and problem solving mathematical students', one of the learning approaches that can improve this ability is a contextual approach. This study aims to examine the differences in upgrades mathematical understanding and problem solving among students receiving contextual learning approach and students who received conventional teaching. In addition revealed the attitude of students towards learning with contextual approach. This study is a quasi-experimental research design pre-test post-test control group design. The population is all eighth grade students MTsN Beureunuen by taking samples of the two classes (class experiment with contextual approaches and control class with conventional learning) through purposive sampling of six parallel classes available.Data collecting using a test instrument of understanding and problem solving abilities as well as a questionnaire scale student attitudes to learning with contextual approach. To see the differences between experimental group students’ with the control group used the t-test with a significance level of 0.05 after testing prerequisites are met. The results showed that an increase in the ability of understanding and solving mathematical problems students obtain contextual learning approach is better than the students who obtain conventional teaching. Based on the analysis of student attitude scale showed a positive attitude towards learning with contextual approach.